Independent Production of Regular Portland Cement Assessed by Simulation and Net Present Value: Produksi Mandiri Semen Portland Biasa dievaluasi melalui simulasi dan Nilai Sekarang Bersih (NPV) - Nugroho, Tito Dwi; Iriani, Iriani (Indonesian Journal of Innovation Studies, 2025)
General background: Ensuring supply continuity and efficiency in cement distribution is a critical challenge for manufacturing companies. Specific background: PT. S faces a strategic decision between producing Ordinary Portland Cement (OPC) in-house or purchasing from external suppliers. Knowledge gap: Previous studies often assess make-or-buy decisions in general terms but rarely integrate operational simulations with financial feasibility for cement distribution. Aims: This study evaluates the comparative feasibility of in-house OPC production versus external purchasing by analyzing demand forecasting, production capacity, distribution performance, and economic outcomes. Results: Using Discrete-Event Simulation (DES), the study finds that a two-day pre-production strategy meets demand of 1,803 tons with a trailer cycle time of 89.9 minutes and effective loading duration of 7 hours and 35 minutes. Net Present Value (NPV) analysis reveals that the in-house option yields Rp2.16 billion, outperforming the buy option’s negative Rp3.18 billion. Novelty: The integration of DES with NPV offers a robust framework for linking operational efficiency and financial viability in cement supply chain decisions. Implications: The findings indicate that in-house production is the more feasible option, providing higher financial returns, reducing supplier dependency, and strengthening operational resilience. Highlights: In-house OPC production outperforms external purchasing financially. DES + NPV integration provides a novel decision-making framework. Strategy strengthens supply continuity and operational resilience. Keywords: Make or Buy, OPC Cement, Discrete Event Simulation, Distribution Strategy, NPV Analysis